Routledge handbook of yoga and meditation studies - Newcombe, Suzanne; O'Brien-Kop, Karen (Abingdon, Oxon ; New York, NY : Routledge, 2020)
The Routledge Handbook of Yoga and Meditation Studies is a comprehensive and interdisciplinary resource, which frames and contextualises the rapidly expanding fields that explore yoga and meditative techniques. The book analyses yoga and meditation studies in a variety of religious, historical and geographical settings. The chapters, authored by an international set of experts, are laid out across five sections: Introduction to yoga and meditation studies History of yoga and meditation in South Asia Doctrinal perspectives: technique and praxis Global and regional transmissions Disciplinary framings In addition to up-to-date explorations of the history of yoga and meditation in the Indian subcontinent, new contexts include a case study of yoga and meditation in the contemporary Tibetan diaspora, and unique summaries of historical developments in Japan and Latin America as well as an introduction to the growing academic study of yoga in Korea. Underpinned by critical and theoretical engagement, the volume provides an in-depth guide to the history of yoga and meditation studies and combines the best of established research with attention to emerging directions for future investigation. This handbook will be of interest to multidisciplinary academic audiences from across the humanities, social sciences and sciences.
OCLC-licensed vendor bibliographic record.
Keywords: Yoga; Meditation